Food Coping Strategies dan Aplikasi Pemantau Status Gizi Sebagai Upaya Preventif Stunting - Berliana Devianti Putri; Nur Septia Handayani; Fitri Retrialisca; Riris Medawati; Imroatul Hafidzah; Rahmi Romadhona Salsabila Putri (Jurnal Abdimas Kesehatan (JAK), 2022)
Stunting is a chronic nutritional deficiency prone to occur in children due to a lack of nutritional intake for a long time starting before the mother is pregnant and until the child is two years old. It is necessary to provide information and education about prevention, early detection and efforts to fulfill nutritional needs.This community service activity aims to increase knowledge of stunting early detection, how to prevent stunting, and improve food coping strategies skills in the household by utilizing food ingredients that are easily found in the surrounding environment. The method used is the preparation of a book with the title "Food Coping Strategies as an Efforts to Prevent Stunting" and the development of the Nutrition Status Monitoring Application (APSI) which was carried out in June-July 2022, as well as providing materials, socialization, and demonstration of cooking competition in August 2022 in the Karanganyar village, Bogorejo District, Blora. The number of participants in this activity was 75 people, consisting of mothers of children under five, women of childbearing age, prospective brides, village officials, representatives of sub-districts and health centers. The results of the Wilcoxon signed ranks test showed that the participants' knowledge about stunting increased after participating in this community service activity (p = 0.001). The activity participants also experienced an increase in skills in choosing, processing, and serving nutrient-rich food made from Moringa leaves as a superior potential in Karanganyar Village.